Asymmetric Synthesis of Isoxazol-5-ones and Isoxazolidin-5-ones - Macchia, Antonio; Eitzinger, Andreas; Brière, Jean-François; Waser, Mario; Massa, Antonio (Synthesis, 2020)
Isoxazol-5-ones and isoxazolidin-5-ones represent two important classes of heterocycles, with several applications as bioactive compounds and as versatile building blocks for further transformations. Unlike the parent aromatic isoxazoles, the presence of one or two stereocenters in the ring renders their asymmetric construction particularly important. In this review, starting from the description of general features and differences between these two related compound families, we present an overview on the most important enantioselective synthesis strategies to access these heterocycles. Both chiral metal catalysts and organocatalysts have recently been successfully employed for this task and some of the most promising approaches will be discussed.1 Introduction2 Isoxazol-5-ones as Nucleophiles2.1 Isoxazol-5-ones as C-Nucleophiles2.2 Isoxazol-5-ones as N-Nucleophiles2.3 Isoxazol-5-ones as C-Nucleophiles in Cyclization Processes3 Asymmetric Construction of Isoxazolidin-5-ones3.1 Enantioselective α-Functionalizations of Isoxazolidin-5-ones4 Arylideneisoxazol-5-ones in Conjugated Addition5 Conclusions
Keywords: asymmetric catalysis; organocatalysis; metal catalysts; heterocycles; chiral building blocks